Design of real time intelligent buses notification system for passengers - Muhammad, Rauf (2012)
Waiting passengers at bus stops for their desired buses seems a commonly observed phenomenon. The obvious reason behind is increased personal vehicle, causing traffic jams. The requirement of a reliable public transport monitoring system is actually the outcome from this unnecessary congestion of traffic observed. Since most of the modern technologies for the Intelligent Transportation System (ITS) have developed since more than 15 years. The need of a Global Positioning/ inertial (GPS/INS) augmentation with a reliable communication system stems from the shortcomings of each individual technology. Besides further advancement, the researchers are now developing implementable technologies for the ease of mankind so that problems related to daily life could be solved. In this dissertation, a new real time intelligent public transport movement monitoring system and station reporting based on GPS and succession of RF Radio Chips is presented. From the societal perspective, the major apprehension of this research, under the framework of a public transit network with bus service providers and users, presents detailed technical solutions for different buses' routes with poles apart IDs using multi technologies applied. GPS is selected to achieve the position data. In order to build the most convenient and reliable system, map matching for location data comparison using optimization technique, Design of Experiment (DOE) is applied. Using the techniques, one single route’s coordinates are optimized to single equation, whose output is the bus stop number in accordance to the bus stop coordinates received. The equation is obtained after a number of run through simulation and then successfully trained to the MCU. Road networks are one of the important surveillance tools in the proposed transport navigation system. In the proposed system, a careful and implementable deployment (hundreds of meters apart) of the ranging sensors is suggested for the cost-effective multi ID buses information at their particular bus stops. These are made configured to create a dedicated network for individual bus ID. Thereby, the extraordinary quality can be shown which is realized by the described algorithms. The experimental results show the promising outcomes. The statistical analysis of equation provides up to 98% efficiency while the designed prototype showed a remarkable agreement between the simulated and actual results. The proposed system surely have the ability to improve the comfortable visibility of moving vehicle at another node as well its smooth and linear transmission to the bus stations by sophisticated transceiver modules, which led people to take a decision either to wait for bus or not. This system can also be supportive to change the trend of people from using their own vehicles to public transport, which lead to solve major problem related to energy consumption, environment and traffic congestion